Geographic altitude and prevalence of underweight, stunting and wasting in newborns with the INTERGROWTH‐21st standard - Jorge Ivan Martínez; Estela M. Román; Emma L. Alfaro; Carlos Grandi; José E. Dipierri (Brazilian Society of Pediatrics, 2019)
Objective: To assess the prevalence and risks of underweight, stunting and wasting by gestational age in newborns of the Jujuy Province, Argentina at different altitude levels. Methods: Live newborns (n  =  48,656) born from 2009-2014 in public facilities with a gestational age between 24+0 to 42+6 weeks. Phenotypes of underweight (<P3 weight/age), stunting (<P3 length/age) and wasting (<P3 body mass index/age) were calculated using Intergrowth‐21st standards. Risk factors were maternal age, education, body mass index, parity, diabetes, hypertension, preeclampsia, tuberculosis, prematurity, and congenital malformations. Data were grouped by the geographic altitude: ≥2.000 or <2.000 m.a.s.l. Chi‐squared test and a multivariate logistic regression analysis were performed to estimate the risk of the phenotypes associated with an altitudinal level ≥2.000 m.a.s.l. Results: The prevalence of underweight, stunting and wasting were 1.27%, 3.39% and 4.68%, respectively, and significantly higher at >2.000 m.a.s.l. Maternal age, body mass index >35 kg/m2, hypertension, congenital malformations, and prematurity were more strongly associated with underweight rather than stunting or wasting at ≥2.000 m.a.s.l. Conclusions: Underweight, stunting, and wasting risks were higher at a higher altitude, and were associated with recognized maternal and fetal conditions. The use of those three phenotypes will help prioritize preventive interventions and focus the management of fetal undernutrition. Resumo: Objetivo: Avaliar a prevalência e os riscos de recém‐nascidos abaixo do peso, baixa estatura e emaciação por idade gestacional da Província de Jujuy, Argentina, em diferentes níveis de altitude. Métodos: Recém‐nascidos vivos (n = 48.656) nascidos entre 2009 e 2014 em instalações públicas entre 24+0‐42+6 semanas de idade gestacional. Os fenótipos de abaixo do peso (< P3 peso/idade), baixa estatura (< P3 comprimento/idade) e emaciação (< P3 índice de massa corporal/idade) foram calculados com os padrões do INTERGROWTH-21st. Os fatores de risco foram idade materna, escolaridade, índice de massa corporal, paridade, diabetes, hipertensão, pré‐eclâmpsia, tuberculose, prematuridade e malformações congênitas. Os dados foram agrupados pela altitude geográfica: ≥ 2.000 ou < 2.000 m.a.s.l. O teste qui‐quadrado e a análise de regressão logística multivariada foram feitos para estimar o risco dos fenótipos associados ao nível de altitude ≥ 2.000 m.a.s.l. Resultados: A prevalência de abaixo do peso, baixa estatura e emaciação foi de 1,27%, 3,39% e 4,68%, respectivamente, significativamente maiores em > 2.000 m.a.s.l. A idade materna, índice de massa corporal > 35 kg/m2, hipertensão, malformações congênitas e prematuridade foram mais fortemente associados a abaixo do peso e não a baixa estatura ou emaciação em ≥ 2.000 m.a.s.l. Conclusões: Os riscos de abaixo do peso, baixa estatura e emaciação foram maiores em altitude mais elevada e foram associados a condições maternas e fetais reconhecidas. O uso desses três fenótipos ajudará a priorizar as intervenções preventivas e focar no manejo da desnutrição fetal. Keywords: Fetal growth retardation, Newborn, Birth weight, Prematurity, Malformations, Palavras‐chave: Retardo do crescimento fetal, Recém‐nascido, Peso ao nascer, Prematuridade, Malformações